FLYWHEEL GENERATOR - Yuniarsih, Pratitis; Bachtiyar, Fahmi; Rosyidin, Mufti; Prabawanto, Trisakti (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Lately, the needs of energy is increasing but its availability is very limited. Therefore,it is important to do more research on energy reform. Generator is one of the alternative energy which commonly used by the public, but it has a minus value such as the voltage instability and low efficiency of the generator . Based on those issues,so we made an application flywheel in electrical generator, which aims to produce a concept of power efficiency increase, stabilize the output voltage of the generator and begin to process power plant. How to operate it is by connecting the outlet of electricity, then TPDT converted to first position (position I), when the indicator light on the generator turns on, TPDT converted into the second position (position II) and began to process power plant.Making process of flywheel application machine in electrical generator start from designing of flywheel mechanims, find the amount of rotation per minute from generator (by experiments), find element of machine which uses(shaft,pin, chain, sprocket, bearing and flywheel), the value of power and the output value of generator. from the results of design of the machine is needed a 700watt with 1500 rpm motor with a transmission system using chain no.25, 10,5 kg mass of flywheel, and the maximum output power from generator 1200watt for 12 minutes. Keywords: Electrical generators, Flywheel,